UTILIZATION OF KECOMBRANG FRUIT PEEL (Etlingera elatior (Jack) RMSm) AS A MOUTHWASH TO PREVENT MOUTH ULCERS AND DENTAL CARIES - Rahmadina, Rahmadina; Mayasari, Ulfayani (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Kecombrang fruit is used by the community as a food ingredient but actually the skin of this kecombrang fruit can be used as a mouthwash for the development of dental caries. This study aims to evaluate the preparation of mouthwash formulations with the addition of kecombrang fruit peel extract. The work procedure starts from extraction, phytochemical testing, antimicrobial testing of extracts, and evaluation of mouthwash preparations. The results contained secondary metabolites in the form of alkaloids, fla-vonoids, tannins, and saponins. Evaluation of mouthwash preparation with pH test is 5.0-5.6, organoleptic test which does not change significantly, viscosity test at 20% and 30% concentration is 1.0193 cP and 1.0061 cP, and antimicrobial test with inhibi-tion diameter on Streptococcus mutans and Candida albicans is 11.3 mm and 11.1 mm. In conclusion, mouthwash with added extracts can inhibit the growth of microbes that cause mouth ulcers and tooth decay.